Frankenstein, slaughterhouses, and blood. Issue 12 (2nd December 2021) - Kaczmar, Dawn
ABSTRACT: We know that the creature in Frankenstein must be a human/animal hybrid because Victor visits slaughterhouses for materials. But what was Victor gathering from slaughterhouses? And what did slaughterhouses evoke for nineteenth-century readers? I demonstrate that slaughterhouses were associated with death, disease, and especially blood. With no running water, drainage, and poor waste management systems, blood cascaded through the streets. This history suggests that Victor and nineteenth-century audiences would have likely seen slaughterhouses as a resource for blood. I present histories of slaughterhouses and blood transfusion experiments that produce a matrix of meaning: in the context of the slaughterhouses, blood signifies death, disease, and immorality; in the context of blood transfusion experiments, blood signifies life, health, and virtue. Both contexts are integral to understanding Frankenstein : Victor's initial motivation is to discover a means to 'renew life where death had apparently devoted the body to corruption.' When he brings the creature to life, Victor effectively uncouples death and 'corruption': the creature is alive, but its corruption – which I trace to the slaughterhouse – remains intact. Although blood transfusion experiments were imagined as bestowing life, health, and virtue, what Victor creates invigorates disease and corruption: life in a 'corrupted' body.